THE SPHERE OF HIGHER EDUCATION AS A COMPONENT OF THE RECOVERY PLAN OF UKRAINE - Юрій Вітренко; Вікторія Ворона; Марія Дебич (National Academy of Educational Sciences of Ukraine, 2022)
The article analyzes the Recovery Plan of Ukraine (draft) in "Education and Science" direction, laid out in "Higher Education" section, and the main indicators of the higher education sphere of Ukraine in 2005-2020. The analysis of the indicators of the higher education sphere of Ukraine in 2005-2020 provides sufficient grounds for the forecast that the dynamics of the students population in 2022-2032 will continue decreasing (by 1.5-2.0 times by 2032). The main priorities for determining the scope of training of higher education specialists in higher education institutions of Ukraine with payment for production and provision of services in the field of higher education at the expense of the state and regional budgets of Ukraine are recommended, which should be taken into account when making up the Recovery Plan of Ukraine in "Education and Science" direction. Proposals to the Recovery Plan of Ukraine in "Education and Science" direction, "Higher Education" section, and to legal acts regulating the higher education sector activities have been made.